Optimalisasi Faktor e-Government Berkelanjutan di Kementerian Sekretariat Negara: Kajian Literatur - Aulia Setyabudi; Teguh Kurniawan (Sawala : Jurnal Administrasi Negara, 2021)
Aims of e-Government implementation can provide benefits in the work process and serve the public. At least, it will have an efficient, effective and accountable impact as well as improve the quality of government services to stakeholders. To achieve this, e-Government initiatives must be sustainable. The study aims to discuss the implementation surrounding sustainability of e-Government at the State Secretariat Ministry through its driving factors. This study uses qualitative research methods through literature study. The study results show the formulation of a holistic and forward-looking e-Government strategy in terms of norms, values, culture, regulations and policies as well as institutions. This strategy needs to be supported by sustainable management of resource factors in the form of funding, information-communication technology, people both staff and leaders. The service quality orientation factor, both internal and public, is also the third driving factor. This relates to performance, usability, reliability, satisfaction and flexibility in meeting needs. Finally, continuous adaptation according to the needs and capabilities of the organization, one of which is through continuous monitoring and evaluation. These factors can be optimized in order to achieve a sustainable e-Government so that the final target can be obtained.